Wellness, mood, sleep, and performance in a women's national basketball team during international competition - Bird, S. P.; Parsons-Smith, R. L.; King, R.; Terry, P. C. (Journal of Human Kinetics, 2025)
The purposes of this study were to examine relationships between athlete self-report measures of wellness, mood, sleep, and performance indicators of a women's national basketball team during international competition (2023 FIBA Women`s Asia Cup). Physical and psychological wellness were recorded using a cloud-based athlete management system, mood was assessed using the 24-item Brunel Mood Scale (BRUMS), and performance was evaluated by player self-assessment and the National Basketball Association`s (NBA) player efficiency score. Wellness indicators were rated at or either side of a normal rating (i.e., 3 on a 1-5 scale), as was self-rated performance. Mean sleep duration was 8:13 hours (± 1:13), with large individual differences in retiring time and sleep duration. Mood scores showed a general pattern of declining tension and vigour over the 14-day assessment period. Mood subscales predicted 49.0% of variance in wellbeing scores, 46.8% of variance in preparedness scores, and 26.0% of variance in player efficiency scores. Wellbeing indicators predicted 34.9% of self-rated performance variance and mood subscale scores predicted 27.7% of variance. These findings suggest that female athletes may be particularly susceptible to mood disturbances impacting performance and highlight the potential for targeted interventions, including stress management and sleep optimization, to mitigate these stressors and support mental wellbeing. These strategies may enhance both psychological health and athletic performance during the high stress demands associated with international competition.